2014
DOI: 10.1158/1078-0432.ccr-13-1759
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein, CYP3A, and Plasma Carboxylesterase Determine Brain and Blood Disposition of the mTOR Inhibitor Everolimus (Afinitor) in Mice

Abstract: Purpose: To clarify the role of ABCB1, ABCG2, and CYP3A in blood and brain exposure of everolimus using knockout mouse models.Experimental Design: We used wild-type, Abcb1a/1b À/À , Abcg2 À/À , Abcb1a/1b;Abcg2

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 41 publications
6
36
0
Order By: Relevance
“…Recently, Tang et al reported that carboxylesterase 1c (Ces 1c) was highly upregulated in Abcb1a/1b and/or Abcg2 knockout mice, and the plasma Ces 1c could tightly bind to everolimus inducing higher plasma stabilization and retention. 33 A similar phenomenon also appears to occur in this study with EPZ005687 and EPZ-6438 as plasma concentrations in knockout mice were about 20-fold higher than in WT mice, whereas the liver, kidney, heart and lung concentrations in wild-type and knockout mice were quite comparable. This indicates that some factor(s) affect the blood-to-tissue relationship of EPZ005687 and EPZ-6438 in knockout mice compared to WT mice.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, Tang et al reported that carboxylesterase 1c (Ces 1c) was highly upregulated in Abcb1a/1b and/or Abcg2 knockout mice, and the plasma Ces 1c could tightly bind to everolimus inducing higher plasma stabilization and retention. 33 A similar phenomenon also appears to occur in this study with EPZ005687 and EPZ-6438 as plasma concentrations in knockout mice were about 20-fold higher than in WT mice, whereas the liver, kidney, heart and lung concentrations in wild-type and knockout mice were quite comparable. This indicates that some factor(s) affect the blood-to-tissue relationship of EPZ005687 and EPZ-6438 in knockout mice compared to WT mice.…”
Section: Discussionsupporting
confidence: 82%
“…The brain-to-plasma ratio is 0.04, which is close to the fraction of blood that is present in the brain vasculature and that will end up in the brain homogenate (39). Similarly, as shown before for the rapamycin analogue everolimus, the much higher levels of rapamycin in the plasma of the knockout strains is most likely due to the instability of rapamycin in plasma (31) and binding of rapamycin to carboxyl esterase 1c (Ces 1c), which protects rapamycin from degradation. Higher plasma levels in knockout mouse strains were also observed with AZD8055 and NVP-BEZ235, albeit that the effect size was much smaller.…”
Section: Discussionsupporting
confidence: 65%
“…1D). Recent work with rapamycin's analogue everolimus has demonstrated that carboxyl esterase 1c is more abundantly present in ABC-transporter knockout mice and responsible for enhanced stability in plasma (31). It is very likely that the higher blood level of rapamycin in knockout mice is similarly caused by avid binding of rapamycin to a serum factor, possibly Ces1c, which is more abundantly present in the plasma of knockout mice.…”
Section: Abcb1 Severely Impairs the Brain Penetration Of Rapamycinmentioning
confidence: 99%
“…The brain disposition of another TKI, crizotinib, was substantially and similarly increased (14-fold) in Abcb1a/1b-and Abcb1a/1b;Abcg2-knockout mice, whereas no effect was observed of deletion of Abcg2 alone (Chuan et al, 2014). Similar results were found with the mammalian target of rapamycin (mTOR) inhibitor everolimus, where brain concentrations and brain-to-liver ratios were substantially increased in Abcb1a/1b-and Abcb1a/1b;Abcg2-knockout mice, but not in Abcg2-knockout mice (Tang et al, 2014).…”
Section: Drugs Only Affected By Abcb1a In Their Brain Accumulationsupporting
confidence: 61%